2020
DOI: 10.3389/fpsyt.2020.00575
|View full text |Cite
|
Sign up to set email alerts
|

Altered Effective Connectivity in Schizophrenic Patients With Auditory Verbal Hallucinations: A Resting-State fMRI Study With Granger Causality Analysis

Abstract: Purpose Auditory verbal hallucinations (AVH) are among the most common and prominent symptoms of schizophrenia. Although abnormal functional connectivity associated with AVH has been reported in multiple regions, the changes in information flow remain unclear. In this study, we aimed to elucidate causal influences related to AVH in key regions of auditory, language, and memory networks, by using Granger causality analysis (GCA). Patients and Methods Eighteen patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Structural connectivity research identified various white-matter pathways including the superior longitudinal fasciculus (arcuate fasciculus), middle longitudinal fasciculus, inferior fronto-occipital fasciculus, extreme capsule, external capsule and uncinate fasciculus that connect Broca’s area with the superior and middle temporal gyri as well as with the inferior parietal lobe (supramarginal and angular gyri) (Axer, Klingner, & Prescher, 2013; Glasser & Rilling, 2008; Kellmeyer et al, 2013; Parker et al, 2005; Powell et al, 2006; Saur et al, 2010). Studies of effective connectivity of Broca’s area also delineated functional connectivity profile of this region both during resting state (Gao et al, 2020), and during various tasks including inhibitory control (Guha et al, 2020), speech production (Eickhoff, Heim, Zilles, & Amunts, 2009) and language processing (den Ouden et al, 2012; Schmithorst, Holland, & Plante, 2007; Sonty et al, 2007), highlighting the causal associations between Broca’s area and various cortical and subcortical regions. Importantly, this body of research underscored the connection between Broca’s area and the posterior superior temporal cortex (Wernicke’s area), providing convergent evidence, together with structural connectivity findings, for the primary role of this loop for language processing (den Ouden et al, 2012; Schmithorst et al, 2007; Sonty et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Structural connectivity research identified various white-matter pathways including the superior longitudinal fasciculus (arcuate fasciculus), middle longitudinal fasciculus, inferior fronto-occipital fasciculus, extreme capsule, external capsule and uncinate fasciculus that connect Broca’s area with the superior and middle temporal gyri as well as with the inferior parietal lobe (supramarginal and angular gyri) (Axer, Klingner, & Prescher, 2013; Glasser & Rilling, 2008; Kellmeyer et al, 2013; Parker et al, 2005; Powell et al, 2006; Saur et al, 2010). Studies of effective connectivity of Broca’s area also delineated functional connectivity profile of this region both during resting state (Gao et al, 2020), and during various tasks including inhibitory control (Guha et al, 2020), speech production (Eickhoff, Heim, Zilles, & Amunts, 2009) and language processing (den Ouden et al, 2012; Schmithorst, Holland, & Plante, 2007; Sonty et al, 2007), highlighting the causal associations between Broca’s area and various cortical and subcortical regions. Importantly, this body of research underscored the connection between Broca’s area and the posterior superior temporal cortex (Wernicke’s area), providing convergent evidence, together with structural connectivity findings, for the primary role of this loop for language processing (den Ouden et al, 2012; Schmithorst et al, 2007; Sonty et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Structural connectivity research identified various white matter pathways including the superior longitudinal fasciculus (arcuate fasciculus), middle longitudinal fasciculus, inferior fronto‐occipital fasciculus, extreme capsule, external capsule, and uncinate fasciculus that connect Broca's area with the superior and middle temporal gyri as well as with the inferior parietal lobe (supramarginal and angular gyri) (Axer et al., 2013 ; Glasser & Rilling, 2008 ; Kellmeyer et al., 2013 ; Parker et al., 2005 ; Powell et al., 2006 ; Saur et al., 2010 ). Studies of the effective connectivity of Broca's area also delineated the functional connectivity profile of this region both during resting state (Gao et al., 2020 ), and during various tasks including inhibitory control (Guha et al., 2020 ), speech production (Eickhoff et al., 2009a ), and language processing (den Ouden et al., 2012 ; Schmithorst et al., 2007 ; Sonty et al., 2007 ), highlighting the causal associations between Broca's area and various cortical and subcortical regions. Importantly, this body of research underscored the connection between Broca's area and the posterior superior temporal cortex (Wernicke's area), providing convergent evidence, together with structural connectivity findings, for the primary role of this loop for language processing (den Ouden et al., 2012 ; Schmithorst et al., 2007 ; Sonty et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effective connectivity (EC), which gives the directional or causal relationships among brain regions is more important for the exploration of the underlying brain mechanisms [2]. The understanding of the directionality of brain networks provides insights into the diagnosis and treatment of neurological or mental diseases such as Alzheimer's disease [3], schizophrenia [4] and addiction [5] etc.…”
Section: Introductionmentioning
confidence: 99%